Ageism in Slovenia - Gerdina, Otto (Annales. Series historia et sociologia, 2024)
Ageism is one of the most widespread forms of discrimination in Europe and one of the mechanisms for generating social inequalities, which is why it is essential to monitor its prevalence. This paper compared the prevalence of ageism in Slovenia in 2008 and in 2022 based on data from round four of the European Social Survey (ESS 2008) and the ESS web panel survey Cronos-2 (2022). The comparison showed that attitudes towards older people remained relatively positive, that there was an increase in the proportion of people who reported perceiving ageism and that there was a slight increase in awareness of the magnitude of the problem. At the three focus points we observed, gender emerged as a key demographic variable with a statistically significant impact.
Keywords: Diskriminacija; Evropska družboslovna raziskava; javno mnenje; primerjalna analiza; spletni panel Cronos-2; Starizem